2008
DOI: 10.1097/sap.0b013e318133a87b
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Facial Fracture Etiologies

Abstract: The medical records of 437 patients with 929 facial fractures were retrospectively analyzed. Fracture patterns were classified based on the presence or absence of fractures in each of 4 anatomic subunits (frontal, upper midface, lower midface, and mandible). The most common etiology of trauma was assault (36%), followed by motor vehicle collision (MVC, 32%), fall (18%), sports (11%), occupational (3%), and gunshot wound (GSW, 2%). The most common fracture type was nasal bone fracture (164). MVC was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
177
3
22

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(209 citation statements)
references
References 16 publications
7
177
3
22
Order By: Relevance
“…The reported major causes of facial fractures vary according to the status of development. Developed countries experience a decrease of road traffic accidents thanks to traffic laws enforcement and motor vehicles safety devices while there is an increase of assaults related to alcohol consumption [4,6,18]. In the studies from developing countries, road traffic accidents are classically reported to be the main aetiology [3,7,9,10,12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported major causes of facial fractures vary according to the status of development. Developed countries experience a decrease of road traffic accidents thanks to traffic laws enforcement and motor vehicles safety devices while there is an increase of assaults related to alcohol consumption [4,6,18]. In the studies from developing countries, road traffic accidents are classically reported to be the main aetiology [3,7,9,10,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…1). Epidemiology of facial fractures varies with era and geographic, socioeconomic, and cultural factors [3][4][5][6]. Classically, interpersonal violence is reported as their leading cause in the industrialized world [4,6] while road traffic accidents are predominant in developing countries [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…1 Darba sekonder olarak meydana gelen yüz kırıklarının, alkol ve diğer maddelerin kullanımı ile ilişkisi vardır. Darp olgularının çoğunun incelenen bu popülasyonda sadece tek bir yüz segmentini içeren yaralanmaya neden olmuştur ve bu muhtemelen yüze yumruk veya bir objeyle tek bir vuruş sonucu oluşmaktadır.…”
Section: Discussionunclassified
“…Similar to the ear, the nose is highly susceptible to injury due to its exposed and unprotected position. Nasal fractures account for half of all facial fractures [5]. In addition, malformations of the nose and ear are found in congenital disorders that are characterized by facial malformations, such as Treacher Collins syndrome and Apert syndrome [6,7].…”
Section: Introductionmentioning
confidence: 99%